Overview of Serum Uric Acid Levels in Adolescents with Overweight and Obesity - Thothilath Sampan (International Journal of Science and Society, 2019)
Nowadays, obesity has become a serious problem world-wide. Obesity can cause the emergence of various kinds of diseases; one of them is hyperuricemia. This condition could found in obese adult as well as in obese adolescence. This study was aimed to obtain the serum uric acid level profile among high school students with overweight and obesity. This was a descriptive study with a cross sectional design. Subjects were students of Gen Panteleon High School with body mass index (BMI) >85. There were 23 students involved in this study. The results showed that 60.87% subjects had hyperuricemia. Most adolescence with obesity tend to have uric acid level above normal value.